APLIKASI TQM DALAM PENGELOLAAN PENDIDIKAN - Abdorrakhman Gintings (Universitas Muhammadiyah Makassar, 2009)
Educational system that managed by any institutions should be seen as an obligation given by all of the educational stakeholders in the country. Ofcourse, the people trust must be returned back to the community by providing the best educational services by which all partises could be delighted. In this context, the quality of education that can fully satisfied the stakeholders is a zero defect practical educational system. This perfect educational system could only be established by managing the educational system; input, process, dan output, that is orientated to a quality standard. This aproach is well known as Total Quality Management or simply just TQM. This paper present the discussion on the understanding, background, strength, and the application strategy of TQM into educational management system including its relationship with BOMM (Bantuan Operational Management Mutu or Operational Subsidy for Quality Management).